A decision framework for identifying models to estimate forest ecosystem services gains from restoration - Zachary L. Christin (Forest Ecosystems, 2016)
Restoring degraded forests and agricultural lands has become a global conservation priority. A growing number of tools can quantify ecosystem service tradeoffs associated with forest restoration. This evolving “tools landscape” presents a dilemma: more tools are available, but selecting appropriate tools has become more challenging. We present a Restoration Ecosystem Service Tool Selector (RESTS) framework that describes key characteristics of 13 ecosystem service assessment tools. Analysts enter information about their decision context, services to be analyzed, and desired outputs. Tools are filtered and presented based on five evaluative criteria: scalability, cost, time requirements, handling of uncertainty, and applicability to benefit-cost analysis. RESTS uses a spreadsheet interface but a web-based interface is planned. Given the rapid evolution of ecosystem services science, RESTS provides an adaptable framework to guide forest restoration decision makers toward tools that can help quantify ecosystem services in support of restoration. Keywords: Decision support, Ecosystem services, Forest restoration, Modeling, Valuation, Comparative tools assessment